1999
DOI: 10.1021/jm980499w
|View full text |Cite
|
Sign up to set email alerts
|

An Effort To Understand the Molecular Basis of Hypertension through the Study of Conformational Analysis of Losartan and Sarmesin Using a Combination of Nuclear Magnetic Resonance Spectroscopy and Theoretical Calculations

Abstract: Losartan is the first recently approved drug against hypertension disease that competes with the biological action of angiotensin II (AII) at the AT1 receptor. Its design was based on the mimicry of the C-terminal segment of AII. Due to the biological significance of Losartan, its structure elucidation and conformational properties are reported as determined by NMR spectroscopy and computational analysis. In addition, molecular modeling of the peptide Sarmesin [Sar1Tyr(OMe)4AII], a competitive antagonist of AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 35 publications
3
83
0
1
Order By: Relevance
“…On the other hand, the two conformers of 3-methyl-1H-tetrazol-3-ium-5-aminide differ in energy by 17.2 kJ mol -1 , because in conformer A the repulsion between the aminide and tetrazole-ring hydrogen atoms is absent. The imine tautomer exhibits both NH and NCH 3 . For this tautomer, the relative energies of the two conformers were also found to be influenced by the presence (in the less stable conformer A) or absence (in the more stable conformer B) of the repulsion between the imine and tetrazole-ring hydrogen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the two conformers of 3-methyl-1H-tetrazol-3-ium-5-aminide differ in energy by 17.2 kJ mol -1 , because in conformer A the repulsion between the aminide and tetrazole-ring hydrogen atoms is absent. The imine tautomer exhibits both NH and NCH 3 . For this tautomer, the relative energies of the two conformers were also found to be influenced by the presence (in the less stable conformer A) or absence (in the more stable conformer B) of the repulsion between the imine and tetrazole-ring hydrogen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] From a fundamental point of view, tetrazoles are also particularly interesting systems, especially because of the tautomerism they may exhibit and their diversified photochemistry. 1,[21][22][23][24][25][26][27][28][29] Unsubstituted tetrazole, for example, was found to exist exclusively in the crystalline phases as the 1H-tautomer, [30][31][32] whereas in solution and gas phase 1H-and 2H-tautomers coexist, the population of the most polar 1H form increasing with the polarity of the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The doublet resonating at 6.86 ppm and assigned to 12 0 and 16 0 protons is correlated through coupling with the doublet at 7.04 ppm. Such correlation is evident also with Losartan molecule that contains biphenyltetrazole segment [32]. As the integration of the doublet shows the existence of three protons, the other one is assigned to H18 0 .…”
Section: Structure Elucidation Of Analog 12bmentioning
confidence: 58%
“…The two different patterns of biphenyl rings are observed in our previous studies using commercial and synthetic ARBs. In Losartan [32], Valsartan [33] and Eprosartan [34] the A ring shows clearly the doublet of doublet pattern common for 1,4 bis-substituted aromatic compounds. However, in the synthetic analog V8 a singlet peak is observed that is attributed to the same ring [17,35].…”
Section: Structure Elucidation Of Analog 12bmentioning
confidence: 96%